Nonlinear Distortion Effects of Vibration-Sensing Interferometric Radar Systems Due to Self-RCS - Tegowski, Bartosz; Koelpin, Alexander (25th International Microwave and Radar Conference, MIKON 2024, 2024)
This contribution investigates the accuracy of interferometric continuous-wave radars depending on their own radar cross section (self-RCS) in the context of mechanical vibration analysis. The self-RCS is determined by the overall physical entity of the system including the radar antenna as well as the housing. The backscattering by the radar re-illuminates the target, which ultimately leads to a nonlinear dependency between its motion and the measured phase. This nonlinear distortion is studied in theory and validated by measurements demonstrating phenomena such as harmonic generation and intermodulation, which depend on the self-RCS.
Created from Fastlane, Scopus look-up
Keywords: Accuracy; continuous-wave (CW) radar; harmonics; interferometric radar; intermodulation; nonlinear effects; radar cross section (RCS)